Geographic shifts in the highland cooking banana (Musa spp., group AAA-EA) production in Uganda - Gold, Clifford S.; Karamura, Eldad B.; Kiggundu, Andrew; Bagamba, Fred; Abera, Agnes M. K. (International Journal of Sustainable Development & World Ecology, 1999)
Between 1970 and 1990 Uganda witnessed the decline of the highland cooking banana from traditional growing areas in the central region, coupled with crop expansion in the country's southwest. Apprehension that the factors leading to loss ofsustainability in the central region may be replayed in extant production areas has raised concern about the future of the cooking banana in Uganda. Consequently, a multi-disciplinary study was conducted at nine central and six southwestern sites to document shifts in cooking banana production and to elucidate the causes behind these shifts. Cooking banana production in central Uganda sites fell from 18% of total food crop and 7% of total cash crop production in the 1970s to 4% and 2%, respectively, in the 1990s. Farmers identified reduced labour availability and management, increasing pest pressure and declining soil nutrient status as the major causes of decline. On-farm verification confirmed farmers' observations: weevil levels were the highest yet found in Uganda, while foliar samples indicated deficiencies in magnesium, nitrogen, and potassium. Soil nutrient deficiencies, however, appear to be a direct outcome of reduced management rather than 'soil exhaustion' as postulated by farmen. . In southwestern Uganda, the importance of the cooking banana as a cash crop has quadrupled since 1970. Banana fint penetrated the region because' of its ease of production and stability of yield. High yields attracted traders and urban market demand drove further crop expansion. With current market incentives, banana management standards have been high. Under current levels of management, it is unlikely that farmen in southwestern Uganda will experience a similar process of decline as that which occurred in the central region. However, concern remains aboqt lack of replenishment ofnutrients leaving the farm in the form offruits sold for market, a nutrient loss which may eventually lead to non-sustainability of the cropping system.